Klasifikasi Kekerasan Batugamping Berdasarkan Nilai Kuat Tekan di Kecamatan Ponjong, Kecamatan Semanu, dan Kecamatan Tanjungsari, Kabupaten Gunung Kidul, Yogyakarta - Rety Winonazada; Listiyawati Nugraha; S. Koesnaryo (Retii, 2020)
In mining and civil fields, knowing the hardness and strength of rock materials is very important to avoid mistakes in geotechnical planning. Rock strength values ​​can be obtained from direct field testing using a Schmidt Hammer or through laboratory testing such as uniaxial compressive strength. Based on previous research, only the uniaxial compressive strength value can be known the hardness of the rock being tested. The research method used is to analyze the results of the limestone compressive strength test data in Gunung Kidul from several previous research journals and from laboratory tests conducted by the author. Based on the analysis, limestone hardness in Ponjong, Semanu, and Tanjungsari Subdistricts according to the Bieniawski classification are in the Soft and Very Soft categories. Meanwhile, according to the Tamrock classification, it is classified in the Soft category with a Mohs scale of 2-3 and Fairly Soft with a Mohs scale of 3-4.5 and poor roughness. And according to the classification of Attawell and Farmer, it belongs to the Very Weak and Weak categories. The range of limestone compressive strength values ​​in the three districts is generally between 10 - 40 MPa.